Atitudes e saberes dos formadores de professores e acadêmicos de pedagogia acerca da educação matemática na educação infantil - Silva, Dilene Kátia Costa da (2018)
Knowledge Teachers and Attitudes regarding Mathematics of Teachers and Academics of the Course of Pedagogy in the process of Initial Formation to work in Early Childhood Education (EI) is the object of this exploratory research, with a qualitative approach. The theoretical basis for the Teaching Training was: Nóvoa (1995), Cury (2004), Brzezinsky (2010), Imbernón (2011), Fiorentini and Castro (2003), among others, on Teaching Knowledge, Shulman (1986), Tardif (2002) e Tardif e Raymond (2004) and as regards attitudes towards Mathematics, Gonçalez (1995, 2000), Brito (1996), Moron (1998), Pirola (2015), Tortora and Pirola (2012), Moraes and Pirola (2015), among others. It was chosen as a problem to investigate: in what terms Knowledge and Attitudes regarding Mathematics present themselves in the formation in Pedagogy, Institutions of Higher Education, in the work with Mathematics, in Early Childhood Education? The locus were two public IES, with the participation of 15 Academics of Pedagogy and 3 Teachers Teachers. The methodological procedures consisted of: Documentary Analysis of legal provisions on Teacher Training, Pedagogical Projects of the Courses (PPC) of Pedagogy and Course Plans of Teachers of IES and Analysis of the instruments: Scales of Attitudes and Questionnaires. The results regarding Initial Formation to teaching in the EI were: Amapá presents a smaller number of adequately trained teachers in the Amazon Region; in the analysis of the PPC of the IES, few theoretical and practical disciplines, focused on EI and Mathematics, were observed, with very small hours. In the analysis of the Teaching Plans, in its contents about mathematical knowledge, the Early Childhood Education deserves some attention, but it is not seen as sufficient to provide the academic of the Pedagogy Course, with consistent theoretical and methodological elements for the work with Mathematics, in the EI. As for Academic Teachers' Knowledge 6, they report that the knowledge acquired in the Course contributed little to EI, with Mathematics, while the 9 reveal good acquisitions to future teaching in Kindergartens and Pre-Schools. The Formators point out the importance of the mastery of mathematical knowledge by the Academics; unanimously indicate the use of concrete materials for a meaningful learning of mathematical knowledge; reveal the overcoming of the lack of training for the EI, as well as several theoretical and methodological foundations used in its classes, addressing aspects pertinent to teaching in IE. As for the results on Attitudes towards Mathematics 3 Formators and 8 Academics have positive attitudes and 7 Academics have negative attitudes. In view of the results, the thesis is defended that Attitudes and Knowledge related to the teaching of Mathematics are necessary aspects to be mediated/focused pari passu in the initial formation, specifically between Teacher Trainers and Academic Pedagogy, aiming at better structuring of knowledge and skills in the process of teacher training in Early Childhood Education. Thus, the results of this thesis can help in the promotion of reflections within the Pedagogy Courses of the various IES and the establishment of public policies that promote the improvement of the Initial Formation of the future teachers of the initial process of Mathematics Education, together with the infants and children of Education Child.